Energy aware medium access control for CPS-based wireless networks. (2016) - Sultana, H. Parveen; Krishna, P. Venkata; Yenduri, Sumanth; Ray, Lydia
Cyber physical systems (CPSs) are an emerging area of research. Medium access control (MAC) plays a major role in improving the performance of a wireless system involved in CPS. In this paper, we try to refine the process of MAC to increase the performance level of CPS-based wireless networks. Though CPS is a combination of different networks, an attempt had been made to create flexibility in the traditional backoff mechanism. We have implemented an energy efficient backoff methodology called as energy hashed virtual backoff algorithm (EHVBA) for a CPS-based wireless networks. This algorithm uses energy as one of the parameters in the existing VBA-CS to increase the CPS's efficacy. However there is a need to bring adaptability to the conventional backoff process in wireless networks. The proposed approach is compared with the similar existing approach in a heterogeneous network's environment. Components like MAC efficiency and energy consumption are elevated to a certain percentage comparatively with existing procedure.